AXIOLOGICAL COMPONENT OF VOCATIONAL TRAINING (THE EXAMPLE OF BACHELOR PROGRAMS IN THE FIELD OF THE GARMENT INDUSTRY PRODUCTS DESIGN) - Lyudmila V. Rosnovskaya (Obrazovanie i Nauka, 2015)
The aim of the article is to review and study the significance of an axiological component and its mechanisms implementation for bachelor vocational training in the field of designing garment industry products.Methods. The methods involve theoretical analysis of philosophical, psychological and pedagogical literature, as well as modeling and classification methods.Scientific novelty and results. An independent axiological component based on structural and content analysis of a clothes designer’s professional work is identified; the content of this component is justified and determined. The substantive characteristics of clothes designer professional competencies are determined in terms of the axiological component. The education objectives aimed at forming the axiological component of Bachelors’ of garment design competencies are classified in correlation with the functions of training. Activity-related information and specifications necessary for values related to actual practice are identified, including channels and mechanisms of translation values in the vocational education process. A model of the educational situation is elaborated, which is proposed to be used as an orientation basis for designing specific educational situations, adequate to this or that kind of value experience. The dialogue activity is shown as the most favorable environment and a form of student activities organization in the development of emotionally-valuable experience.Practical significance. The article is supposed to be used while the training process for the garment industry and the fashion industry staff.